If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1y) + 2y = -26 (x * 5 + -1y * 5) + 2y = -26 (5x + -5y) + 2y = -26 Combine like terms: -5y + 2y = -3y 5x + -3y = -26 Solving 5x + -3y = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 5x + -3y + 3y = -26 + 3y Combine like terms: -3y + 3y = 0 5x + 0 = -26 + 3y 5x = -26 + 3y Divide each side by '5'. x = -5.2 + 0.6y Simplifying x = -5.2 + 0.6y
| 7x-(3x-4)=8-6x-6+5x | | log(7)=2 | | 14.40+4.05p=4.50(3+p) | | y=13x+404+46 | | 3(3x-6)=1-2x | | x+(x-10)+2(x-10)+6=100 | | 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) | | -5.99+23.105x=-587.72x-54.936 | | 36-yi=4x+3i | | (x+2)=-(x-3) | | 5y=11x+6 | | f(x)=2x+3x-1 | | x^2-4x=x(7+x) | | -(x+2)=-(x-3) | | 12m^2-17m-5= | | 15-4x+16=11 | | -6x+15=18x-7 | | 0=-r+6 | | 0=[r+6] | | -(3x+1)=-5 |